2019
DOI: 10.1101/867192
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Distinct architecture and composition of mouse axonemal radial spoke head revealed by cryo-EM

Abstract: 1The radial spoke (RS) transmits mechanochemical signals from the central pair 2 apparatus (CP) to axonemal dynein arms to coordinate ciliary motility. The RS head, 3 directly contacting with CP, differs dramatically in morphology between protozoan and 4 mammal. Here we show the murine RS head is compositionally distinct from the 5 Chlamydomonas one. Our reconstituted murine RS head core complex consists of 6 Rsph1, Rsph3b, Rsph4a, and Rsph9, lacking Rsph6a whose orthologue exists in the 7Chlamydomonas RS head… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 67 publications
2
3
0
Order By: Relevance
“…Our comparative analyses suggest that RPSH4A –/– cilia exhibit more severe RS defects, with the remnant of the stalk structures of RS1 and RS2 appearing shorter than those of RSPH1 –/– cilia in a larger proportion of axonemal repeats ( Figures 2 and 3, G and H ; Supplemental Figure S2; Supplemental Movie S1). These data support a model in which RSPH4A is more centrally located within the RS head than RSPH1, potentially reaching into the arch region or interacting strongly with arch proteins, in agreement with recent findings ( Zheng et al , 2021 ; Grossman-Haham et al. , 2020 ; Gui et al.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our comparative analyses suggest that RPSH4A –/– cilia exhibit more severe RS defects, with the remnant of the stalk structures of RS1 and RS2 appearing shorter than those of RSPH1 –/– cilia in a larger proportion of axonemal repeats ( Figures 2 and 3, G and H ; Supplemental Figure S2; Supplemental Movie S1). These data support a model in which RSPH4A is more centrally located within the RS head than RSPH1, potentially reaching into the arch region or interacting strongly with arch proteins, in agreement with recent findings ( Zheng et al , 2021 ; Grossman-Haham et al. , 2020 ; Gui et al.…”
Section: Discussionsupporting
confidence: 92%
“…These data support a model in which RSPH4A is more centrally located within the RS head than RSPH1, potentially reaching into the arch region or interacting strongly with arch proteins, in agreement with recent findings (Wei Zheng, 2019;Grossman-Haham et al, 2020;Gui et al, 2020). This is consistent with IHC data that demonstrates loss of RSPH4A results in the loss of RSPH1; while the loss of RSPH1 does not result in the loss of RSPH4A (Frommer et al, 2015).…”
Section: Discussionsupporting
confidence: 91%
“…Based on these observations and the structural homology between RSP4 and RSP6, and between RSP1 and RSP10, we propose that the human RS head center has tissue-specific compositions, containing different sets of homodimers, namely RSP4HA, RSPH9 and RSPH1 in ciliated epithelia, and RSP6HA, RSPH9 and RSP10HB in sperm. Supporting this hypothesis, recombinantly expressed RSP4HA, RSPH1 and RSPH9 could form a stable structure composed of a globular core and two long MORN extensions, in the absence of RSP6HA and RSP10HB 38 . The two tissue-specific human RS heads might confer unique regulatory activities in the beating of axonemes in these different cell types.…”
Section: Discussionmentioning
confidence: 76%
“…Noticing the CCT6-HR exhibited obvious preferred orientation problem, we then adopted the stage tilt strategy to collect additional tilted data (Fig. S6A, Table1) (Tan et al, 2017), which has been shown to help to overcome the preferred orientation problem in cryo-EM study of various complexes (Xu et al, 2020; Zheng et al, 2021). Noteworthy, CCT6-HR displays compositional heterogeneity, and we obtained an 8- and a 9-meric double ring structure both at open conformation (Fig.…”
Section: Resultsmentioning
confidence: 99%